Spontaneous rupture of an unscarred uterus during second trimester: a rare occurrence - Singh, Anju; Chaudhary, Mamta Kumari; Sikka, Pooja; Singla, Rimpi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The rupture of the uterus is one of the most serious obstetric complications a pregnant uterus can experience. Most ruptured uteri are associated with one or more risk factors and occur more frequently during the third trimester. As an obstetric emergency, it requires a high level of suspicion for prompt diagnosis and urgent intervention due to its life-threatening nature. We reported a 29-year-old primigravida without any known risk factors presenting with abdominal pain and vomiting at 20 weeks of pregnancy. Ultrasonography (USG) revealed free fluid in the paracolic gutter and Morrison’s pouch with a live intrauterine fetus. An exploratory laparotomy was planned in view of tachycardia and anemia. During laparotomy, hemoperitoneum was observed, and there was a 5 cm transverse fundal rent with placenta popping out from it. Emergency surgical management, including removal of the placenta and fetus along with fundal repair, was performed, and the patient recovered well. Symptoms such as acute abdominal pain during pregnancy should alert the surgeon to the possibility of uterine rupture, even in the absence of known risk factors. A prompt diagnosis and immediate intervention are crucial for achieving a good outcome in such cases.